2022
DOI: 10.3389/fmicb.2021.800470
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum AR113 Exhibit Accelerated Liver Regeneration by Regulating Gut Microbiota and Plasma Glycerophospholipid

Abstract: Emerging evidence indicates that probiotics have been proved to influence liver injury and regeneration. In the present study, the effects of Lactiplantibacillus plantarum AR113 on the liver regeneration were investigated in 70% partial hepatectomy (PHx) rats. Sprague-Dawley (SD) rats were gavaged with L. plantarum AR113 suspensions (1 × 1010 CFU/mL) both before and after partial hepatectomy. The results showed that L. plantarum AR113 administration 2 weeks before partial hepatectomy can accelerate liver regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 68 Studies have exhibited that increasing TNF-α expression enhanced hepatocyte proliferation and accelerated LR in PHx rats. 69 Zhang et al. reported that MiR-199a was an important regulator of TNF-α signaling pathway, which regulated LR and hepatocyte proliferation in rats by targeting TNF-α/TNFR1 pathway.70 As demonstrated by Lee et al., human placental hydrolyzate (hPH) activated TNF-α pathway through activating TNF-α secretion in KCs, thereby promoting LR in rats.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“… 68 Studies have exhibited that increasing TNF-α expression enhanced hepatocyte proliferation and accelerated LR in PHx rats. 69 Zhang et al. reported that MiR-199a was an important regulator of TNF-α signaling pathway, which regulated LR and hepatocyte proliferation in rats by targeting TNF-α/TNFR1 pathway.70 As demonstrated by Lee et al., human placental hydrolyzate (hPH) activated TNF-α pathway through activating TNF-α secretion in KCs, thereby promoting LR in rats.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“…Similarly, nisin, cecropin, and P. chinense have both the ability to change the abundance and composition of the fish gut microbiota and affect the expression of some anti-inflammatory cytokines, such as TGF-β ( Ke et al, 2021 ). Probiotics such as Lactobacillus plantarum AR113 could influence liver generation by increasing the expression of TNF-α, HGF and TGF-β ( Xie et al, 2021 ). All these experimental results indicate that there are correlations between the gut microbiota and the TGF-β signaling pathway; however, functional gain- and loss-of-function experiments are still lacking to confirm the direct relationship between the gut microbiome or metabolome and the TGF-β signaling pathway.…”
Section: Gut Microbiome and Metabolome And Aamentioning
confidence: 99%
“…Listeria monocytogenes, a pathogenic bacterium can be found in various kinds of food, can enhance the effect of HGF through producing bacterial HGF receptor agonist InlB321/15 and thus promote liver regeneration after 70% PH ( 61 ). Lactiplantibacillus plantarum AR113 administration showed decline of phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidyl serine (PS), and lysophosphatidyl choline (LysoPC) levels in the serum of the rats and increase HGF secretion in liver after 70% PH ( 62 ). Although the correlation of gut microbiota and HGF has been well addressed, the detailed mechanism is need to be further investigated.…”
Section: Gut Microbiota Affects Liver Regeneration By Modulating Cruc...mentioning
confidence: 99%